1992
DOI: 10.1080/01140671.1992.10422328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a forchlorfenuron dip on kiwifruit fruit size

Abstract: All the fruit from kiwifruit vines (Actinidia deliciosa (A.Chev.) CF. Liang et A.R. Ferguson cv.Hayward) were dipped in 10 mgllitre solutions of forchlorfenuron (N-(2-chloro-4-pyridyl)-Nphenylurea) 35 and 36 days after full bloom at two sites in the 1989/90 season and 22 days after full bloom at one site in 1990/91. Growth curves showed that treated fruit grew 30--60% faster than untreated fruit, both during the rapid cell division and expansion phase (fmt 53-74 days after full bloom), and during the subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…At present, dipping fruit in PGRs to increase crop yield has been reported for cucumber, tomato and kiwi fruit in many countries, such as Japan, New Zealand and China . However, to our knowledge, the current study is the first to investigate the combination of fungicides and PGRs in dipping fruit application for the control of cucumber gray mold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, dipping fruit in PGRs to increase crop yield has been reported for cucumber, tomato and kiwi fruit in many countries, such as Japan, New Zealand and China . However, to our knowledge, the current study is the first to investigate the combination of fungicides and PGRs in dipping fruit application for the control of cucumber gray mold.…”
Section: Discussionmentioning
confidence: 99%
“…32 At present, dipping fruit in PGRs to increase crop yield has been reported for cucumber, tomato and kiwi fruit in many countries, such as Japan, New Zealand and China. 18,23,33 However, to our knowledge, the current study is the first to investigate the combination of fungicides and PGRs in dipping fruit application for the control of cucumber gray mold. Our study revealed that dipping fruit in fludioxonil and forchlorfenuron (PGR) is a cost effective practice and has no negative consequences on the environment or human health.…”
Section: Residue Analysis Of Fludioxonil and Forchlorfenuron In Markementioning
confidence: 98%
“…N ‐(2‐chloro‐4‐pyridyl)‐ N ′‐phenylurea (CPPU), a synthetic cytokine (Jáuregui‐Riquelme, Kremer‐Morales, Alcalde, & Pérez‐Donoso, 2017) that promotes cell division and seed germination, is applied to a variety of fruits, such as apple (Matsumoto, Fujita, & Sato, 2018), grape (Jáuregui‐Riquelme et al, 2017), mango (Pujari, Malshe, Shedge, Zagade, & Lawande, 2016), and blueberry (Retamales, Lobos, Romero, Godoy, & Moggia, 2014), and vegetables to increase their volume and yield. CPPU was initially used in the production of kiwifruit in the 1990s, and this treatment improved the fruit yields and brought about great economic benefits (Blank et al., 1992). However, excessive use of CPPU led to reductions in nutrition, rapid softening, and rotting of the fruit during postharvest storage because that the cytokine accelerated the decomposition of pectin and cellulose of cell wall (Cooper, González, & Retamales, 2007; Kim et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…CPPU was initially used in the production of kiwifruit in the 1990s, and this treatment improved the fruit yields and brought about great economic benefits (Blank et al, 1992). However, excessive use of CPPU led to reductions in nutrition, rapid softening, and rotting of the fruit during postharvest storage because that the cytokine accelerated the decomposition of pectin and cellulose of cell wall (Cooper, González, & Retamales, 2007;Kim et al, 2006).…”
mentioning
confidence: 99%
“…FCF is a plant growth regulator, being extensively used for increasing fruit size and weight in watermelon, kiwifruit, grape and apple[ 1 4 ]. In China, the incidence of FCF had caused an adverse impact on the kiwifruit industry.…”
Section: Introductionmentioning
confidence: 99%